WOMEN'S ECONOMIC EMPOWERMENT THROUGH UMKM TOWARDS INDEPENDENCE - Ernawati S. K (EDUSOS: Jurnal Edukasi dan Ilmu Sosial, 2026)
The Micro, Small, and Medium Enterprises (UMKM) sector is currently a medium for strengthening the role of women in poverty alleviation in the national economic development agenda. Women's involvement in this area has been shown to provide room for increased agency and access to financial resources, which in turn can support household well-being and expand the reach of their social participation. This study article aims to describe in depth the tensions that arise when women's economic independence clashes with socio-cultural constructions that continue to place women as the main responsible for domestic affairs. The study approach uses literature studies through various relevant scientific journals according to the study of the problem. The results of the study show that the success of economic empowerment programs is often not able to change the gender structure at the family level proportionally. However, behind the economic success, it was found that the financial independence achieved by women in the public (productive) realm did not necessarily break down the walls of patriarchal culture in the private (reproductive) realm. This condition triggers vulnerability for women to physical and psychological pressure, due to the demand to carry out productive and reproductive roles simultaneously without a balanced division of duties. Therefore, this study emphasizes that the success of women's empowerment should not be measured only through income indicators. Sociocultural transformation is needed that promotes gender equality and a fairer distribution of domestic burdens, as well as more accommodating institutional support for women entrepreneurs.